2007
DOI: 10.1111/j.1747-7379.2007.00078.x
|View full text |Cite
|
Sign up to set email alerts
|

Nativity, Duration of Residence, Citizenship, and Access to Health Care for Hispanic Children

Abstract: This article examines differences in access to a regular source of health care for children of Hispanic subgroups within the United States. Particular attention is paid to the impact of the immigration status of the mother – including nativity, duration in the United States, and citizenship status – and its affect on access to health care for Hispanic children. Data are pooled from the National Health Interview Survey for 1999–2001 and logistic regression models are estimated to compare Mexican American, Puert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 18 publications
3
12
0
Order By: Relevance
“…As a result, at longer durations the composition of the remaining immigrant population will be disproportionately represented by those with poorer health outcomes. Such a pattern is consistent with studies that show, on average, a higher level of healthcare utilization among Mexican immigrants with a longer duration in the US (LeClere et al , 1994, Durden, 2007). …”
Section: Introductionsupporting
confidence: 91%
“…As a result, at longer durations the composition of the remaining immigrant population will be disproportionately represented by those with poorer health outcomes. Such a pattern is consistent with studies that show, on average, a higher level of healthcare utilization among Mexican immigrants with a longer duration in the US (LeClere et al , 1994, Durden, 2007). …”
Section: Introductionsupporting
confidence: 91%
“…Census data show Latinos comprising 22% (16 million) of the US population under the age of 18 years (32). Consistent with studies that have shown that Latino adults and the elderly are less likely to access and utilize health care compared with non-Latino whites and other groups (17, 25, 72, 77, 93, 142), studies have also revealed that Latino youth experience barriers to access and are less likely to utilize health services compared with youth from other racial and ethnic backgrounds (29, 30, 103). In particular, youth who have Mexican-origin parents with low English-language proficiency have worse access to, and lower utilization of, health services and have worse experiences in primary care than children whose parents speak English well or are otherwise more acculturated (13, 35, 50, 94, 103, 126).…”
Section: Health Care Access and Utilization Trends For Latinossupporting
confidence: 61%
“…On the other hand, immigrants with longer residency may have developed the necessary social networks, social ties, and healthcare access that increase the likelihood of staying in the United States. This is consistent with studies showing that immigrants with longer residence in the United States have higher healthcare utilization than those with shorter lengths of residency (Durden 2007;LeClere et al 1994). The results also provide evidence of negative acculturation that takes effect after many years of living in the United States.…”
Section: Discussionsupporting
confidence: 91%